Solid Pseudopapillary Neoplasms of the Pancreas: A Report of Two Cases - Dilip Dan; Rakesh Rambally; Shamir O. Cawich; Ravi Maharaj; Vijay Naraynsingh (Case Reports in Medicine)
Solid pseudopapillary neoplasms of the pancreas are uncommon, accounting for only 1-2% of all pancreatic neoplasms. These tumors are being detected at an increased rate, probably due to the increased awareness and the liberal use of imaging. We report two cases of patients with solid pseudopapillary pancreatic tumors and review the existing literature.